2009
DOI: 10.1007/s00430-009-0108-7
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of influenza A and B in German infants and adolescents

Abstract: The objective of this study was to provide seroepidemiological information on influenza A and B antibodies in children and adolescents. Viral immunoglobulin G antibodies were determined retrospectively using enzyme-linked immunosorbent assays in a group of 1,111 children and adolescents. Sera (809) from healthy adult blood donors served as controls. In children, the prevalence of antibodies against influenza A was 82.0% and against influenza B 9.6%, whereas in adults the prevalence of antibodies against influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
1
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 40 publications
3
45
1
1
Order By: Relevance
“…Testing of defined serum samples from children [2], newborns and their mothers [22] by several commercial ELISAs, including the haemagglutination inhibition assay [23], revealed sensitivities ≥97% and no crossreactivities between influenza A and B virus or to other viral pathogens for the ELISAs used in this study. Both ELISAs were carried out manually and used for qualitative and semi-quantitative antibody testing.…”
Section: Testing Of Seramentioning
confidence: 68%
See 3 more Smart Citations
“…Testing of defined serum samples from children [2], newborns and their mothers [22] by several commercial ELISAs, including the haemagglutination inhibition assay [23], revealed sensitivities ≥97% and no crossreactivities between influenza A and B virus or to other viral pathogens for the ELISAs used in this study. Both ELISAs were carried out manually and used for qualitative and semi-quantitative antibody testing.…”
Section: Testing Of Seramentioning
confidence: 68%
“…To obtain data most widely representative for the whole population of children in Germany, nine different German regions were included. A recently published study on the influenza seroprevalence in Germany included only sera from children who lived in the German federal state Thuringia [2], and the results were not regarded as representative for the entire country. Furthermore, as that study used other serological methods than ours, the results are only comparable to a limited extent.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[104] Data from serologic surveys have demonstrated that 15-45% of children are infected with an influenza virus each year, [105] and by the age of 6, most children have been infected with influenza viruses at least once. [106] Children infected with influenza will shed higher titers of virus during their illness and shed virus for longer periods of time compared with adults. [107,108] This finding, together with high rates of illness, suggests children are critical source in the transmission of influenza in communities and households, and sustain annual epidemics.…”
Section: Disease Burdenmentioning
confidence: 99%